Efeitos demográficos e educacionais no desemprego jovem das Regiões Metropolitanas do Brasil - Nathália Barbosa Souza e Silva (2020)
Youth unemployment is a relevant topic in labor market studies. This is because such phenomenon has some permanent particularities, such as its high levels, its sensitivity to recessionary periods and its characteristics of influencing the adult labor market. Among the discussions of the determinants of youth unemployment, which go through demographic, economic, institutional and structural matters, O'Higgins (2001) points out three main causes of unemployment for this population subgroup, namely: (i) variation in aggregate demand, (ii) relative wages, represented by youth signaling in the labor market and (iii) the relative size of youth cohorts. From this framework, this paper is expected to answer some questions that became the main objective of this dissertation. How does the current downward trend in youth cohort impact youth unemployment? What are the effects of the general increase in population education on unemployment, and would such effects be uniform across educational subgroups? Are the structural and economic factors of the economy responsible for determining unemployment? To this end, this dissertation presents monitoring of the proportion of unemployed young people by educational groups from 2001 to 2015 through data from the Pesquisa Nacional por Amostra de Domicílios (PNAD). From the adoption of a decomposition method proposed by DasGupta (1994), it is expected to quantify the weight of each of the determinants of youth unemployment on the time differential observed among the proportions of unemployed by the educational group. Therefore, The objective is to evaluate the change in this determination through intensification of age and educational transitions and the economic cycles, always taking regional differentials as a guide. The results show that youth unemployment responds positively to the variations resulting from the reduction of youth participation for all the decompositions made. Regarding the educational transition, the results indicate that youth unemployment behaves differently according to schooling groups, penalizing the most educated and benefiting the least educated. Besides, the educational component played a leading role in determining the temporal differences of unemployed youth people in the North and Northeast Metropolitan Regions. Economic variations also influence the determination of unemployment, but with greater participation for the South and Southeast Regions.